Remarks on Modern Standard Arabic Construct State and Quantification - (:unkn) unknown (My University, 2020)
This thesis investigates the interpretations of genitive and quantificational forms that Modern Standard Arabic (MSA) unifies under a complex DP, namely Construct State (CS). Despite the linguistic differences between these phenomena, the PF form of this structure neutralizes all indicated types and their sub-types into a head-complement form (possessum-possessor or quantifier-domain restriction), where the whole structure’s definiteness is recovered from the complement that is distinguished for this value overtly. However, the internal syntactic and semantic components such as the source of relations and definiteness value of the whole structure that contribute to the CS its various interpretations are always concealed at PF. This neutralization makes it hard to view the differences between CS types as well as the causes of their various semantic ambiguities. This project analyzes Nominal and Quantificational CSs of MSA to uncover their hidden syntactic and semantic factors that distinguish their semantic contributions. To approach these two forms, this thesis consists of four main discussion chapters. Two of these chapters (2&3) are devoted to approach genitive nominals, and their syntactic and semantic aspects. Chapter (2) looks at (in)definiteness: marking, agreement (inheritance), and its interpretation on either component at LF. In this chapter, I argue that the Nominal-CS D head inherits its covert definiteness featural specifications from its complement whose definiteness is distinguished overtly. This inheritance takes place at the syntactic level via the operation of syntactic agreement (following Pesetsky and Torrego, 2007 framework) which feeds the semantic interpretations of this form, regardless of some exceptional cases for this inheritance. Chapter (3) investigates the semantic ambiguities of a nominal CS. One type of the ambiguities categorizes a CS as possessive vs. modificational CS based on the relation between the head and the complement. Fol-lowing Borer (2009), these interpretations are caused by the referentiality of the complement, which is associated with its syntactic category: a referential DP for the possessive type and non-referential NP for modificational type. Another ambiguity is caused by the relation between the nominals in the distinguished types contributed by Relator Phrase (RP) projection (cf. Den Dikken, 2006 and Ouhalla, 2011). The head of this projection denotes a free variable over contextual relations (possessiveness, agent, control, or other pragmatic relations) or its relation can be contributed lexically by the head noun when it is relational semantically. However, the lexical relation may or may not feed the RP projection depending on the context. Regarding the quantificational side of the investigation, it focuses on quantificational determiners and their domain restriction (DR) nouns that form the quantificational construct state (QCS), in addition to some notes about scope taking ambiguities. Chapter (4) approaches the quantifiers kul: “every/each or all” dʒami:ʔ “all” muʕðˤam “most” baʕdˤ “some” and their DR nouns in CS. All the former quantifiers are restricted by definite plural DPs without partitive preposition, except for the distributive interpretation of kul:. For the latter, it has to be restricted by an indefinite bare noun. Regarding these issues, this chapter argues that quantifiers of Arabic are not syntactic deter-miners since they are distinguished for (in)definiteness overtly in non-CS structure or covertly in QCS. The account that is drawn for the quantifiers with definite DR proposes that they are partitive quantifiers whose partitive relation is established by a null PartP (partitive phrase) (cf. Fehri, 2018). PartP allows them to quantify over parts of the individual sum denoted by their definite plural DR noun. On the other hand, the inherited definiteness on the quantifiers is semantically vacuous since the domain of quantification is restricted by the definiteness of DR noun. For the distributive interpretation of the universal kul: “every/each”, its DR is a bare NP whose number contributes the (non)atomic granularity for distributivity rather than categorizing it as indefinite since this language lacks the indefinite determiner. The following chapter shifts the discussion toward some notes on scope taking to examine the possibility of the covert inverse scope and inverse linking readings at LF in SVO and VSO word orders. For the inverse scope at clause-level, the findings of this chapter analysis suggest that the scope is fluid with respect to VSO order, while the SVO order shows some exceptions. The subject of SVO occurs in the left periphery as a topic or focus (Soltan, 2007; Albuhayri, 2019) where QR does not exceed (cf. May, 1977, 1985; Heim and Kratzer, 1998). Merely, a clitic left dislocated topic can freeze the scope by reserving wide scope interpretation, while a focused subject can show scope ambiguity due to its ability to reconstruct because it is a moved element to the left periphery. Regarding scope linking within DP, MSA allows this type of QR movement at LF, but, still, the left periphery boundary is respected.
Keywords: Complex DP; Construct State; Genitive; Modern Standard Arabic; Quantification; Quantifiers